TAFSIR AL-QURAN DALAM PERSPEKTIF PENDIDIKAN AKHLAK - Ali Akbar; Intan Aulia (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
many human beings are intelligent and intellectual but possess unpraiseworthy morals/character (akhlak), leading them to misuse the intelligence they possess. This indicator has become a portrait of the unbalancing act between intellectual development and moral development. Morality/Character towards Allah (Akhlak to Allah) can be interpreted as the attitude or actions that should be performed by humans as creatures, towards Allah as the creator. These attitudes or actions have the characteristics of moral actions as mentioned above, thus, instilling morality in the child's soul by providing true guidance and useful advice so that the teachings they receive permeate their soul. When it has integrated, it will form a personality within them that constantly performs noble deeds, goodness, and a fondness for working for the benefit of the homeland, the state, and the nation.